2014
DOI: 10.1186/1756-0500-7-656
|View full text |Cite
|
Sign up to set email alerts
|

Leydig cell tumors of the testis: a case report

Abstract: BackgroundLeydig cell tumors are the most common non-germ cell gonadal tumors with apparent increased incidence in the last few years. They are usually benign tumors. We report a case of Leydig cell tumor of testis in a patient presenting atypical features.Case presentationA 29-year-old Caucasian man, born with right cryptorchidism, corrected without medical treatment before the age of two years, was diagnosed with Leydig cell tumor. Two years after diagnosis was identified moderately elevated estradiol serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Despite the favorable outcome of one patient 4 years after his orchietomy, elevated estradiol and retroperitoneal lymph node swellings were observed . Another study also reported a patient who presented with a hormone‐secreting interstitial tumor of the testis and who developed metastasis 7 years after the removal of a benign primary tumor .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite the favorable outcome of one patient 4 years after his orchietomy, elevated estradiol and retroperitoneal lymph node swellings were observed . Another study also reported a patient who presented with a hormone‐secreting interstitial tumor of the testis and who developed metastasis 7 years after the removal of a benign primary tumor .…”
Section: Discussionmentioning
confidence: 96%
“…Immunohistochemically, the tumor cells were positive for inhibin-alpha and Melan-A ( Figure 3C Despite the favorable outcome of one patient 4 years after his orchietomy, elevated estradiol and retroperitoneal lymph node swellings were observed. 5 Another study also reported a patient who presented with a hormone-secreting interstitial tumor of the testis and who developed metastasis 7 years after the removal of a benign primary tumor. 6 In conclusion, Leydig cell tumors are rare and show variable endocrinological findings, depending on their ability to secrete steroid hormones.…”
Section: Case Reportmentioning
confidence: 99%
“…[23,24] Tumor markers differentiate testicular malig-nancy before one can stick to endocrinal syndrome. Pure LCT do not produce any tumor markers [23,24] as it occurred in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Leydig cell tumor is a rare germ cell tumor that originates from gonadal stroma, accounting for about 15 to 3% of testicular neoplasms in adults and about 4% in pediatric patients who have not yet reached maturity (1). Leydig cells are named after Franz Leydig.…”
Section: Introductionmentioning
confidence: 99%